Evaluation of different protocols using antimicrobial photodynamic therapy with curcumin and blue led light control of Escherichia coli in vitro - Muniz, Igor Pereira Ribeiro; Calado, Stefano Pedro de Melo; Ribeiro, Israel Souza; Galantini, Maria Poliana Leite; Gonçalves, Caroline Vieira; Rosa, Luciano Pereira; Rosa, Francine Cristina Silva; Silva, Robson Amaro Augusto da (Acta Scientiarum. Biological Sciences, 2024)
Escherichia coli (E. coli) is a gram-negative bacterium extremely relevant in the context of public health, being involved in the development of several diseases worldwide. The main treatment available for infections caused by E. coli is the use of antibiotics. However, several strains of this bacterium have shown resistance to available antibiotics, necessitating the development of alternative treatment methodologies. In this scenario, Antimicrobial Photodynamic Therapy (aPDT) emerges as an excellent viable alternative to antibiotic use. This study aimed to standardize protocols based on aPDT utilizing curcumin as photosensitizer activated by blue LED light for the control of E. coli in vitro. Curcumin solutions of 60, 80, and 100 μg mL-1 were made and photoactivated by blue LED light with fluencies of 6.6, 13.2, and 19.8 J cm-2. E. coli (ATCC® 25922 ™) was cultured for 24 hours at 37 °C. Bacterial suspensions of 1.5 x 106 CFU mL-1 were exposed to aPDT treatments. Control groups were established for each light dose and curcumin concentration. Protocols using 80 and 100 μg mL-1 curcumin solution with19.8 J cm-2 irradiation effectively inhibited bacterial growth, suggesting significant antibacterial activity (p-value < 0.05), and are recommended for this purpose.